The emotional context of self-management in chronic illness: A qualitative study of the role of health professional support in the self-management of type 2 diabetes - Dunbar James; Sulaiman Nabil; Dunning Trisha; Blackberry Irene; Walker Christine; Furler John; Best James; Young Doris (BMC, 2008)
Abstract Background Support for patient self-management is an accepted role for health professionals. Little evidence exists on the appropriate basis for the role of health professionals in achieving optimum self-management outcomes. This study explores the perceptions of people with type 2 diabetes about their self-management strategies and how relationships with health professionals may support this. Methods Four focus groups were conducted with people with type 2 diabetes: two with English-speaking and one each with Turkish and Arabic-speaking. Transcripts from the groups were analysed drawing on grounded hermeneutics and interpretive description. Results We describe three conceptually linked categories of text from the focus groups based on emotional context of self management, dominant approaches to self management and support from health professionals for self management. All groups described important emotional contexts to living with and self-managing diabetes and these linked closely with how they approached their diabetes management and what they looked for from health professionals. Culture seemed an important influence in shaping these linkages. Conclusion Our findings suggest people construct their own individual self-management and self-care program, springing from an important emotional base. This is shaped in part by culture and in turn determines the aims each person has in pursuing self-management strategies and the role they make available to health professionals to support them. While health professionals' support for self-care strategies will be more congruent with patients' expectations if they explore each person's social, emotional and cultural circumstances, pursuit of improved health outcomes may involve a careful balance between supporting as well as helping shift the emotional constructs surrounding a patient life with diabetes.